2012
DOI: 10.1021/es302697h
|View full text |Cite
|
Sign up to set email alerts
|

Household Light Makes Global Heat: High Black Carbon Emissions From Kerosene Wick Lamps

Abstract: Kerosene-fueled wick lamps used in millions of developing-country households are a significant but overlooked source of black carbon (BC) emissions. We present new laboratory and field measurements showing that 7–9% of kerosene consumed by widely used simple wick lamps is converted to carbonaceous particulate matter that is nearly pure BC. These high emission factors increase previous BC emission estimates from kerosene by 20-fold, to 270 Gg/year (90% uncertainty bounds: 110, 590 Gg/year). Aerosol climate forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 49 publications
1
118
0
Order By: Relevance
“…Emission sources that have been recently added, or for which the emission calculation has been refined, include flaring of associated petroleum gas in the oil and gas exploration sectors, kerosene lamps for lighting (further development of estimates originally presented by Lam et al, 2012), diesel generator sets, high-emitting vehicles, international shipping, refuse burning, and brick kilns (see Sect. 3).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Emission sources that have been recently added, or for which the emission calculation has been refined, include flaring of associated petroleum gas in the oil and gas exploration sectors, kerosene lamps for lighting (further development of estimates originally presented by Lam et al, 2012), diesel generator sets, high-emitting vehicles, international shipping, refuse burning, and brick kilns (see Sect. 3).…”
Section: Methodsmentioning
confidence: 99%
“…Only after Lam et al (2012) reported very high black carbon emission factors, indicating that this is potentially an important "missing" source, has more work been done to distinguish between kerosene used for cooking and lighting; the new estimates suggest this source might contribute 5-10 % of global BC emissions.…”
Section: Kerosene Lampsmentioning
confidence: 96%
See 3 more Smart Citations